2019
DOI: 10.1111/head.13478
|View full text |Cite
|
Sign up to set email alerts
|

Headaches Attributed to Ischemic Stroke and Transient Ischemic Attack

Abstract: Introduction Although headaches attributed to ischemic strokes and transient ischemic attack occur frequently, they are often overlooked and underdiagnosed as manifestations of cerebrovascular disease. Method This is a narrative review. Results The prevalence of headache attributed to ischemic stroke varies between 7.4% and 34% of cases and of headache attributed to transient ischemic attack, from 26% to 36%. Headache attributed to ischemic stroke is more frequent in younger patients, in migraineurs, in those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 45 publications
(180 reference statements)
4
34
0
1
Order By: Relevance
“…Our results are in accordance with the literature [3] and showed that 15% of ischemic stroke patients had headache at the time of ischemic stroke onset. However, the previous studies did not analyze the exact time of development and disappearance of these headache, and did not have any simultaneous control groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accordance with the literature [3] and showed that 15% of ischemic stroke patients had headache at the time of ischemic stroke onset. However, the previous studies did not analyze the exact time of development and disappearance of these headache, and did not have any simultaneous control groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with the literature [3] and showed that 15% of ischemic stroke patients had headache at the time of TA B L E 3 Types of headache on the day of stroke and the day of interview in controls Migraines with and without aura with altered characteristics and tension headache with altered characteristics, as well as migraines with and without aura and tension headache in the form of a new type of headache, were defined in the text as a migraine-like and tension-type-like headache, respectively, as they can be attributed to stroke.…”
Section: Is Headache Causally Related To Stroke?supporting
confidence: 94%
See 1 more Smart Citation
“…In many of these conditions, such as ischaemic or haemorrhagic stroke, headache is overshadowed by focal signs and/or disorders of consciousness. Headaches associated with ischaemic stroke have no special features, which can be ipsilateral or bilateral, mild to moderate intensity and often recover within 3 months 2. It is more common in posterior circulation than in anterior circulation.…”
Section: Headache Can Manifest As a Major Symptom Of Craniocervical Vmentioning
confidence: 99%
“…Headaches associated with ischaemic stroke have no special features, which can be ipsilateral or bilateral, mild to moderate intensity and often recover within 3 months. 2 It is more common in posterior circulation than in anterior circulation. In haemorrhagic stroke, headache is usually severe and torturous.…”
Section: Headache Can Manifest As a Major Symptom Of Craniocervical Vmentioning
confidence: 99%